Identification of students’ misconception against global warming concept - F Fajarini; S Utari; E C Prima (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Students’ misconception is defined as the students’ understanding concept that is inconsistent with the scientific concepts. These misconceptions commonly occur by either our mind, teacher or textbook. The research aims to analyze students’ misconceptions on the topics of global warming, greenhouse effect and ozone layer depletion. The quantity and the cause of misconceptions was analyzed based on misconception percentages and interviews. The research was conducted in one private school in Bandung. The results showed that there are 17 concepts identified as misconception with 51.3% students acquiring misconception, 37.7% understanding and 11% unknown. The interview has identified the causes of students’ misconceptions due to the invalid information comprehended by the students during a lesson in the class. Consequently, students tend to acquire misconceptions. The research implied that the teachers must elaborate several ways to recover students’ misconceptions. The learning model of process-oriented guided-inquiry learning (POGIL) is proposed to minimize students’ misconception.